PNPLA3, MBOAT7 and TM6SF2 modify mitochondrial dynamics in NAFLD patients: Dissecting the role of cell-free circulating mtDNA and copy number. (March 2023) - Longo, M.; Paolini, E.; Meroni, M.; Ripolone, M.; Napoli, L.; Tria, G.; Maggioni, M.; Moggio, M.; Fracanzani, A.L.; Dongiovanni, P.
Abstract : Background: Mitochondrial (mt) dysfunction is a hallmark of progressive NAFLD. MtDNA copy number (mtDNA-CN) and cell-free circulating mtDNA (ccf-mtDNA), which reflect mt-mass and mt-dysfunction, respectively, are gaining attention for NAFLD non-invasive assessment. We demonstrated that PNPLA3, MBOAT7 and TM6SF2 deficiency in HepG2 cells increased mt-mass, mtDNA-CN and ccf-mtDNA. Aims: To assess the genetic contribution on mt-dynamics, mtDNA-CN and ccf-mtDNA in 1) primary mouse hepatocytes silenced for PNPLA3 / MBOAT7/TM6SF2 genes; 2) Discovery (n=28) and Validation (n=773) cohorts, including biopsied NAFLD patients, stratified according to number of risk variants (NRV=3). Methods: Mt-morphology was assessed by TEM. mtDNA-CN was measured in the entire Validation cohort (n=773), while ccf-mtDNA in a subgroup (n=300) with available serum samples. mtDNA-CN and mt-related genes were evaluated in liver biopsies. Results: Primary mouse hepatocytes challenged with fat overload or PNPLA3/TM6SF2 / MBOAT7 co-silencing lowered mt-fusion paralleled by higher mt-fission and ccf-mtDNA release, suggesting that lipid accumulation and genetics may independently unbalance mt-dynamics. In the Discovery cohort, NRV=3 patients showed the highest mtDNA-CN compared to those with 1-2 or no variants. At TEM, NRV=3 carriers increased mt-mass and presented an elevated pattern of mt-morphological alterations (swollen shapes, double membranes rupture). In the Validation cohort, mtDNA-CN associated with the NAFLD histological spectrum and NRV=3 at multivariate analyses, supporting that both NAFLD severity and genetics may modulate mt-dynamics. In liver biopsies, mtDNA-CN was higher in NRV=3 patients together with reduction of mt-fusion and activation of mt-fission, resembling what observed in hepatocytes. Ccf-mtDNA was augmented in NRV=3 patients with low-moderate/severe NAFLD, thereby sustaining that this effect was amenable to the 3 at-risk polymorphisms. ROC curves showed that mtDNA-CN discriminated NAFLD subjects vs controls (AUC: 0.71), while ccf-mtDNA was highly predictive of NAFLD-HCC vs NALFD (AUC: 0.79). Conclusions: mtDNA-CN and ccf-mtDNA may have pathological and predictive significance in NAFLD patients at high-risk, especially in those genetically-predisposed.